Comparison of Densiron 68 and 1 000 cSt silicone oil in the management of rhegmatogenous retinal detachment with inferior breaks - Ibrahim Kocak (International Journal of Ophthalmology, 2013)
AIM:To compare success rates and complications of Densiron 68 and 1000cSt silicone oil (SO) in the management of rhegmatogenous retinal detachment (RRD) with inferior breaks (IBs).METHODS:Totally 61 eyes of 61 consecutive patients with RRD with IBs were assigned to pars plana vitrectomy (PPV) with Densiron (n=31) or PPV with SO (n=30) in order of presentation. SO and Densiron removal was performed 3 months after initial surgery. Follow up visits were terminated 6 months after SO removal.RESULTS:With a single operation, the Densiron group showed 84% and SO 74% reattachment. With further surgery, both groups showed 90% re-attachment. Complications such as cataract, raised intraocular pressure (IOP), inflammatory reaction, macular epiretinal membranes, and emulsification of SO were seen in both groups.CONCLUSION:Densiron and SO are found to have similar success rates and complications.